(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study was conducted to determine the effect of pollution with hydrocarbons and total heavy metals in soil sites near oil fields in southern Iraq over several distances (center of the field, after 250 meters, after 500 meters) and its relationship with the physical and chemical properties of the soil. The values of petroleum hydrocarbons were higher than the critical limit of 10 mg kg-1, especially in soils close to the source of pollution, and it decreases as we move away from the pollution, up to a distance of 500 meters, and it becomes less polluted. As for the values of heavy metals, especially lead, cadmium, and nickel, they were higher than the critical limit for all distances. The results of the study showed the effect of hydrocarbon pollutants and heavy metals in The oil fields were based on the values of electrical conductivity, where the results ranged between (16.9 - 98) ds m-1, where the highest value of conductivity was in the North Rumaila field and the lowest value in the Nasiriyah field, while the values of the calcium element ranged between (13.75-37.5) mmol L-1.The highest value was in the North Rumaila field and the lowest value was in the Nasiriyah oil field. As for the magnesium element, the results ranged between (16.25-87.5) mmol L-1, where the highest value was in the Nahran Bin Omar field and the lowest value was in the Nasiriyah oil field. As for the sodium element, the results ranged between (105-750) mmol L-1, where the highest value was in the North Rumaila field and the lowest value was in the Nasiriyah oil field. As for the potassium element, the results ranged between (0.46-3.46) mmol L-1, where it was The highest value was in the North Rumaila field and the lowest value in the Nasiriyah oil field.